Turkish Neonatal Society guideline on enteral feeding of the preterm infant - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2019)
Early initiation of enteral feeding with the own mother's milk and prevention of postnatal growth failure is the target of nutrition in preterm infants. Together with total parenteral nutrition, mouth care and minimal enteral nutrition is started with colostrum in the very early hours of life in small preterm infants. Expressed mother's milk is given via a gastric tube and gradually increased in accordance with the gestational age/birth weight and the risk factors. For infants born heavier than 1000 grams, the aim is to reach total enteral feeding at the end of first week, and at the end of the second week for infants weighing less than 1000 grams. Supporting mothers in milk expression and kangaroo mother care, promoting non-nutritive feeding, appropriate fortification of mother' milk, and initiating and advancing breastfeeding as soon as the infant is ready are all crucial. Donor mother milk, and as a second choice, preterm formula is advised if the mother's milk is not available. Individualized post-discharge nutrition decisions can be taken in accordance with the actual growth at the time of discharge. The goal is optimal neuro developmental achievement together with the prevention of long-term metabolic problems. Late preterm infants, which constitute the majority of preterm infants, also need close nutritional attention and follow-up.
Keywords: Enteral; nutrition; preterm; INTENSIVE-CARE-UNIT; HUMAN-MILK; NECROTIZING ENTEROCOLITIS; FORTIFICATION; INDOMETHACIN; PREVENTION; COMMITTEE; OUTCOMES